Neuropeptide F inhibits dopamine neuron interference of long-term memory consolidation in Drosophila - Kuan-Lin Feng; Ju-Yun Weng; Chun-Chao Chen; Mohammed Bin Abubaker; Hsuan-Wen Lin; Ching-Che Charng; Chung-Chuan Lo; J. Steven de Belle; Tim Tully; Cheng-Chang Lien; Ann-Shyn Chiang (iScience, 2021)
Summary: Long-term memory (LTM) formation requires consolidation processes to overcome interfering signals that erode memory formation. Olfactory memory in Drosophila involves convergent projection neuron (PN; odor) and dopaminergic neuron (DAN; reinforcement) input to the mushroom body (MB). How post-training DAN activity in the posterior lateral protocerebrum (PPL1) continues to regulate memory consolidation remains unknown. Here we address this question using targeted transgenes in behavior and electrophysiology experiments to show that (1) persistent post-training activity of PPL1-α2α′2 and PPL1-α3 DANs interferes with aversive LTM formation; (2) neuropeptide F (NPF) signaling blocks this interference in PPL1-α2α′2 and PPL1-α3 DANs after spaced training to enable LTM formation; and (3) training-induced NPF release and neurotransmission from two upstream dorsal-anterior-lateral (DAL2) neurons are required to form LTM. Thus, NPF signals from DAL2 neurons to specific PPL1 DANs disinhibit the memory circuit, ensuring that periodic events are remembered as consolidated LTM.